Openable electromagnetic actuator as a non-contact, agile tool for crimping operations. (August 2015) - Taber, Geoffrey A.; Vivek, Anupam; Coffey, John; Daehn, Glenn S.
Abstract: This work focuses on using electromagnetic forming (EMF) for creating a conformal interference fit between an aluminum outer tube and a coaxially aligned inner part using a novel tool known as an openable actuator, or simply O-actuator. The utility of the O-actuator is in applications where it is impractical or impossible to remove a crimped assembly from a traditional helical actuating coil. In this work, a fully conformal joint between aluminum alloy type 6061 tube of circular starting geometry and AISI 1018 steel hexagonal rod was created with an input electrical energy of 8 kJ.